The Use Of Multimedia In Teaching Vocabulary To The First Grade Students At Smp Muhammadiyah 7 Surakarta In 2014/2015 Academic Year - Aninda, Maulina Indah; , Aryati Prasetyarini, S.Pd, M.Pd; , Siti Fatimah, S. Pd, M. Hum (2015)
This research paper is aimed at answering: (1) the objectives of teaching vocabulary by using multimedia, (2) the materials used in teaching vocabulary by using multimedia, (3) the procedure of teaching vocabulary by using multimedia, and (4) the students' response to the use of multimedia in teaching vocabulary. This study is a descriptive qualitative research. The object of the research is teaching vocabulary using multimedia. The data sources are event, informant and document related to teaching voabulary using multimedia. The technique of data analysis used in this research the writer uses an interactive model. That includes three main components, namely reducing the data, displaying the data and drawing conclusion and verification. The result of this study shows that (1) the objectives of teaching vocabulary using multimedia are the students are interested in the material presented and not being bored, to make teaching-learning process would be more effective and to make the students easy in understanding the lesson materials, to help the students are able to answer the exercises, (2) the material used in teaching vocabulary is suitable with the curriculum, the teaching materials used by the teacher in teaching English using multimedia are animals, things in the house, and things at the school. The material for teaching vocabulary is taken from English book "When English Rings a Bell". Teacher also combines the media, she uses software, pictures, video, audio, and other media, (3) The procedure of using media in teaching vocabulary are pre- teaching, whilst teaching, and closing, (4) the students' response to the use of multimedia in teaching vocabulary is positive in which most of the students become active, motivated to learn, and controlled well. They can also understand the materials well.